2008
DOI: 10.2746/042516408x266060
|View full text |Cite
|
Sign up to set email alerts
|

Post mortemsurvey of dental disorders in 349 donkeys from an aged population (2005–2006). Part 1: Prevalence of specific dental disorders

Abstract: Aged donkeys have a high prevalence of significant dental disease, especially cheek teeth diastemata. These findings highlight the importance of routine dental examinations and prophylactic dental treatments to improve the dental health and welfare of donkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
4
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 13 publications
10
53
4
3
Order By: Relevance
“…Sharp enamel points, however, were found to be significantly higher in donkeys aged 0-10 years old in one study [2] and cheek teeth fractures did not differ significantly among age groups in another study [1]. The current study has also demonstrated a significant linear effect of age on the prevalence of no/mild dental disease where increasing age was associated with a decreasing number of horses assigned to this category [14,18].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Sharp enamel points, however, were found to be significantly higher in donkeys aged 0-10 years old in one study [2] and cheek teeth fractures did not differ significantly among age groups in another study [1]. The current study has also demonstrated a significant linear effect of age on the prevalence of no/mild dental disease where increasing age was associated with a decreasing number of horses assigned to this category [14,18].…”
Section: Discussionsupporting
confidence: 52%
“…Most published equine dental studies have been conducted on clinical cases in hospital settings [10][11][12] or using cadaver material [13][14][15][16], and these have furthered our understanding of the pathophysiology of various dental disorders. Field surveys have a key role in determining the prevalence of oro-dental disorders and providing evidence that will assist veterinary surgeons' and owners' understanding of the impact that dental disease has on equine health and welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Dental abnormalities in horses As a result, 'dental disease' is a term used by the University of Edinburgh group to describe the equine dental condition. The term includes abnormalities such as those above, but excludes SEPs, but does include diastemata and missing teeth (Du Toit et al, 2008a and2009). Clearly, this is still a threat to animal health, with donkeys exhibiting dental disease significantly more likely to have a lower body condition score (Du Toit et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that these abnormalities were incidental and did not cause the death of the zebra, and therefore were not preventing them from eating. This is compared to the 93% occurrence of dental disease in domesticated donkeys in a UK study (Du Toit et al, 2008a) and 62% in a Mexican study (Du Toit et al, 2008b). Domestication, and specifically the use of bits and bridles, has also been suggested to increase the occurrence of oral ulcers in horses, potentially caused by sharp enamel points (SEPs) on cheek teeth (Tell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…That study also identified risk factors for developing impactions, which included old age and dental disease, as well as previous colic episodes (Cox et al, 2007). Du Toit et al (2008) further identified the presence of cheek teeth diastemata as a factor associated significantly with colic-related illness in the donkey.…”
Section: Introductionmentioning
confidence: 99%